Pertumbuhan dan Hasil Padi pada Inseptisol Asal Rawa Lebak yang Diinokulasi Berbagai Konsorsium Bakteri Penyumbang Unsur Hara - Wuriesyliane Wuriesyliane; Nuni Gofar; Abdul Madjid; Hary Widjajanti; Ni Luh Putu SR (Jurnal Lahan Suboptimal : Journal of Suboptimal Lands, 2013)
The aim of this research was to study the effect of multisynergism bacterial isolates growth of rice plants as well as to obtain best composition of endophytic bacterial isolates, Azotobacter, Azospirilium and phosphate solubilizing bacteria in spurring growth of rice plants. This research was conducted in October 2012 to February 2013. This study arranged in a completely randomized design (All treatments of multiple bacterial isolates resulted in increase of soil N x P Content). The results showed that multibacterial isolates B (endophytic bacteria + Azospirillum) increased vegetative and generative growth of rice plants. Treatment G (composition of endophytic bacterial isolates, Azotobacter, Azospirilium and phosphate solubilizing bacteria) can increase rice yields. Some soil N and P content increased in response to all treatments of multiple bacterial isolates. The similar result was also observed in the N and P uptake that some multiple bacterial isolates improved N and P uptake of plants